TINJAUAN PENGELOLAAN LIMBAH DI TAMAN SATWA BALI ZOO SUKAWATI GIANYAR TAHUN 2017 - I Gusti Ayu Aris Wijayanthi; Nengah Notes; I Gusti Ayu Made Aryasih (Poltekkes Kemenkes Denpasar, 2018)
Abstract.Garbage is commonly found in public places which become a public health problem because public place is a meeting place of all kinds of society with all kinds of diseases possessed by the society. Trash is also included in the waste. Where waste is all solid and liquid materials are discharges derived from human activities individually as well as the results of other activity activities. This type of research is used by observation (direct observation) by using descriptive method. Sources of waste contained in Bali Zoo come from visitors or from activities or activities carried out at Bali Zoo Wildlife Park. Where from the implementation of the research obtained results that is on the solid waste management (garbage) obtained results meet the requirements while in the liquid waste is said not to qualify. The conclusion of this research is the number of waste management facilities that need to be considered, such as waste bins that do not have a lid and the absence of waste water treatment plant facilities in Bali Zoo.Keywords: waste, sanitation, wildlife park